2020
DOI: 10.1186/s10086-020-01863-6
|View full text |Cite
|
Sign up to set email alerts
|

Bending properties of dimension lumber produced from Siberian larch (Larix sibirica) in Mongolia

Abstract: The modulus of elasticity (MOE) and modulus of rupture (MOR) were evaluated for 190 pieces of dimension lumber (2 by 4 lumber, 38 by 89 mm in cross-section) produced from Larix sibirica trees grown in Mongolia. The 5% tolerance limits of the MOE and MOR were 5.70 GPa and 15.1 MPa, respectively. The value of the 5% tolerance limit of the MOR exceeded the characteristic value of 2 by 4 lumber in visual grading class No. 3 of the Japanese Agricultural Standard for the D. fir-L, Hem-Tam, JS-III and S-P-F softwood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…These results suggest that high bending properties can be obtained in lumber classified into higher visual grading classes. On the other hand, Tumenjargal et al [13] reported that no significant differences in either the MOE or MOR of 2 by 4 (38 × 89 mm) lumber in L. sibirica were found between SS, No. 1, No.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…These results suggest that high bending properties can be obtained in lumber classified into higher visual grading classes. On the other hand, Tumenjargal et al [13] reported that no significant differences in either the MOE or MOR of 2 by 4 (38 × 89 mm) lumber in L. sibirica were found between SS, No. 1, No.…”
Section: Introductionmentioning
confidence: 95%
“…2 grade in visual grading) for 2 by 6, 2 by 8, 2 by 10, and 2 by 12 cross sections. Recently, Tumenjargal et al [13] reported that f 0.05 values of MOE and MOR in 2 by 4 (38 × 89 mm) lumber of L. sibirica grown in Mongolia were 5.70 GPa and 15.1 MPa, respectively. However, available information on f 0.05 for the MOE and MOR of dimension lumber for structural use remain limited for common softwoods in Mongolia.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations